(untitled) (Communications in Mathematical Research, 2022)
The inverse Lax-Wendroff (ILW) procedure is a numerical boundary treatment technique, which allows finite difference schemes and other schemes to achieve stability and high order accuracy when using cartesian meshes to solve boundary value problems defined on complex computational domain. In this short survey we summarize the main ingredients of the ILW procedure, discuss its applicability and stability properties, and provide possible directions of its future development.